Monsoon-driven Saharan dust variability over the past 240,000 years - Skonieczny, C.; McGee, D.; Winckler, G.; Bory, A.; Bradtmiller, L. I.; Kinsley, C. W.; Polissar, P. J.; De Pol Holz, Ricardo Hernán; Rossignol, L.; Malaize, B. (My University, 2019)
Reconstructions of past Saharan dust deposition in marine sediments provide foundational records of North African climate over time scales of 10(3) to 10(6) years. Previous dust records show primarily glacial-interglacial variability in the Pleistocene, in contrast to other monsoon records showing strong precessional variability. Here, we present the first Saharan dust record spanning multiple glacial cycles obtained using Th-230 normalization, an improved method of calculating fluxes. Contrary to previous data, our record from the West African margin demonstrates high correlation with summer insolation and limited glacial-interglacial changes, indicating coherent variability in the African monsoon belt throughout the late Pleistocene. Our results demonstrate that low-latitude Saharan dust emissions do not vary synchronously with high-and mid-latitude dust emissions, and they call into question the use of existing Plio-Pleistocene dust records to investigate links between climate and hominid evolution.
Keywords: Climate oscillation